If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4.8f + 9 = -5 Reorder the terms: 9 + -4.8f = -5 Solving 9 + -4.8f = -5 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4.8f = -5 + -9 Combine like terms: 9 + -9 = 0 0 + -4.8f = -5 + -9 -4.8f = -5 + -9 Combine like terms: -5 + -9 = -14 -4.8f = -14 Divide each side by '-4.8'. f = 2.916666667 Simplifying f = 2.916666667
| 3x+5=2x-2 | | 3p-200=200-2p | | x+50x=220 | | 4(2n+9)+15n=30n-6 | | x-143+512=745 | | (x+6)(x-9)=-14 | | 4x=3x-1+5+2x | | =x+3y+12+5y | | 2/3-9=6-2/3 | | -2p+(8p-6)=-18 | | 5(4Z-1)-3(2+7)=14(Z+1) | | =2x+9y+6x | | x^2-21x+100=-3x | | 7x=9+8x | | 12-3f=5f+1 | | -16-6w=2(8v-7) | | 4(2n+9)+15n=5n-6 | | -15x-8x=8x+17 | | 9x+-7=8 | | (x+8)*2= | | =4x+x+8 | | 300-2n=120 | | x^5+9x^3=0 | | 6m+5-3=7(m-1) | | 12n-5=9n+3 | | 3(x-5)=-(x+3) | | 100=-(x-1) | | 28a+39-4a=319-11a | | =2x+7+3x | | 16-(6y-7)+3y=5(y+1) | | x^5+9x=0 | | 0=-t^2+6t |